Tracing innate immune defences along the path of Listeria monocytogenes infection. Issue 7 (15th April 2014) - Regan, Tim; MacSharry, John; Brint, Elizabeth
Abstract : The pathogenic gram‐positive bacteria, Listeria monocytogenes is a facultative infectious intracellular pathogen that causes listeriosis. Effective elimination of infection is dependent upon a functioning innate immune system and activation of inflammatory responses by pathogen recognition receptors (PRRs). In this review, we trace the route of L. monocytogenes invasion as it disseminates from the intestinal epithelium, through the bloodstream of the host, to the liver and spleen. Along this route, we highlight the diverse, region specific, innate defences in place throughout the course of infection. We provide an overview of recent advances in our knowledge of key innate immune defences against L. monocytogenes, focusing on the PRRs in various cell types known to be critical in the detection of this pathogen.